Yohimbine-Induced Reactivity of Heart Rate Variability in Unmedicated Depressed Patients With and Without Adverse Childhood Experience - Deuter, Christian Eric; Otte, Christian; Wingenfeld, Katja; Kuehl, Linn Kristina (Frontiers in Psychiatry, 2021)
Stressful life events play a role in the pathogenesis of major depressive disorder (MDD) and many patients with MDD were exposed to developmental stress due to adverse childhood experiences (ACE). Furthermore, dysregulation of the autonomic nervous system and higher incidence of cardiovascular disease are found in MDD. In MDD, and independently in individuals with ACE, abnormalities in heart rate variability (HRV) have been reported. While these are often confounded, we systematically investigated them with a study which included MDD patients with/without ACE as well as healthy individuals with/without ACE. With this study, we investigated the influence of noradrenergic stimulation on HRV reactivity in unmedicated participants in a randomized, double-blind, repeated measures design. Our sample consisted of men and women with MDD and ACE (n = 25), MDD without ACE (n = 24), healthy participants with ACE (n = 27) and without ACE (n = 48). Participants received a 10mg single dose of the alpha-2 antagonist yohimbine that increases noradrenergic activity or placebo on two separate days, with ECG recordings before and after drug administration at defined intervals. We found lower basal HRV in MDD and ACE: patients with MDD had reduced RMSSD whereas participants with ACE had lower LF-HRV. Contrary to our hypothesis, there was no effect of yohimbine. With this study, we were able to replicate previous findings on HRV differences in MDD and ACE. From the null effect of yohimbine, we conclude that the yohimbine-induced sympathetic activation is not a significant driver of HRV in MDD and ACE.